Boosting the Stability of Oxygen Vacancies in α‐Co(OH)2 Nanosheets with Coordination Polyhedrons as Rivets for High‐Performance Alkaline Hydrogen Evolution Electrocatalyst - Jiang, Li‐Wen; Huang, Yuan; Zou, Yang; Meng, Chao; Xiao, Yi; Liu, Hong; Wang, Jian‐Jun (Advanced energy materials, 2022)
The strong alkaline electrolytes are utilized in various key electrochemical applications and the severe corrosion by hydroxyl ions endows the development of high‐performance electrode materials with a great challenge. Here, an effective strategy is demonstrated to stabilize α‐Co(OH)2 under harsh alkaline electrochemical condition by coordination polyhedron pinning (MoO42−, WO42−) on the surface for hydrogen evolution reaction (HER). The addition of MoO42− in 1 m KOH can inhibit the attack of hydroxyl ions on oxygen vacancies in α‐Co(OH)2, and simultaneously modulate the electronic structure of active sites for HER. The theoretical calculations and experimental results reveal that MoO42− can be riveted on the surface of α‐Co(OH)2 to greatly stabilize oxygen vacancies and inhibit the formation of soluble ions of Co(OH)3−. The resultant active sites exhibit reduced maximum energy barriers for the optimized alkaline HER. Additionally, MoO42− near the interface between α‐Co(OH)2 and electrolyte can alleviate the accumulation of hydroxyl ions on α‐Co(OH)2 due to the electrostatic repulsion, improving the stability toward HER. This work offers insight into the role of coordination polyhedron ions in regulating and enhancing the stability of α‐Co(OH)2 for various potential electrochemical applications in alkaline electrolyte. The strong alkaline electrolytes are utilized in various key electrochemical applications and the severe corrosion by hydroxyl ions endows the development of high‐performance electrode materials with a great challenge. Here, an effective strategy is demonstrated to stabilize α‐Co(OH)2 under harsh alkaline electrochemical condition by coordination polyhedron pinning (MoO42−, WO42−) on the surface for hydrogen evolution reaction.